Stimulus probability affects the visual N700 component of the event-related potential. Issue 3 (March 2020) - Althen, H.; Banaschewski, T.; Brandeis, D.; Bender, S.
Highlights: The event-related visual occipito-temporal N700 component is sensitive to stimulus probabilities. Visual P1, N1, N700, but not P3, showed larger amplitudes to rare than frequently presented letters. N700 sensitivity to probabilities might reflect an orienting response on the level of visual cortex. Abstract: Objective: To examine whether the occipito-temporal visual N700 component of the event-related potential is sensitive to stimulus probabilities. Methods: P1, N1, P3, and, in particular, the occipito-temporal N700 component of the event-related potential were analysed in response to frequent and rare non-target letters of a continuous performance task in 200 healthy adolescents. Additionally, amplitude habituation with time was examined for the occipito-temporal N700 and N1 components. Results: The visual P1, N1, and occipito-temporal N700 components were significantly larger in response to rare letters than to frequent letters, whereas the P3 component demonstrated no amplitude difference. Over time, the occipito-temporal N700 amplitude decreased in response to the rare letters, while the N1 amplitude increased, to both, frequent and rare letters. Conclusions: This study provides first evidence that the visual occipito-temporal N700 is sensitive to stimulus probabilities, suggesting an enhanced post-processing of rare stimuli in secondary visual areas. The distinct habituation patterns of occipito-temporal N700 and N1 amplitudes distinguish repetition effects on stimulus post-processing (N700) from those on perception (N1). Significance: The enhanced N700 component to rare stimuli might reflect an orienting response and underlying attentional processes. The N700 sensitivity to stimulus probabilities should be examined in patient groups with attentional deficits.